2020
DOI: 10.1007/s00405-020-06313-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative quantification of floating mass transducer coupling quality in active middle ear implants: a multicenter study

Abstract: Purpose Evaluating the effectiveness of intraoperative auditory brainstem responses (ABRs) to stimulation by the Vibrant Soundbridge (VSB) active middle ear implant for quantifying the implant's floating mass transducer (FMT) coupling quality. Methods In a diagnostic multicentric study, patients (> 18 years) who received a VSB with different coupling modalities were included. Pre-and postoperative bone conduction thresholds, intraoperative VSB-evoked ABR thresholds (VSB-ABR) using a modified audio processor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 34 publications
2
31
0
2
Order By: Relevance
“…Saturation in VSB evoked ABR wave-V latencies most likely occurred to due limited dynamic range of the audio processor used for signal transmission. It was already reported in the study investigating the relation between L ABR and coupling efficiency that the audio processor output saturated between 35 and 40 dB nHL stimulation level depending on gain settings [see Figure 1 in ( 27 )]. Stimulation levels at threshold level L ABR were perceived by the patient as very soft sounds.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Saturation in VSB evoked ABR wave-V latencies most likely occurred to due limited dynamic range of the audio processor used for signal transmission. It was already reported in the study investigating the relation between L ABR and coupling efficiency that the audio processor output saturated between 35 and 40 dB nHL stimulation level depending on gain settings [see Figure 1 in ( 27 )]. Stimulation levels at threshold level L ABR were perceived by the patient as very soft sounds.…”
Section: Discussionmentioning
confidence: 96%
“…The total offset between VSB evoked wave-V latencies and normative data for acoustic stimulation was most likely caused by a signal processing delay in the audio processor. Reference data for acoustic click stimulation were used here due to technical measurements which showed that the CE-chirp used for stimulation emerged as a click-like stimulus after transmission through the audio processor and VSB ( 24 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations